Experimental Investigation of Emulsions Formation and Evolution in Pipeline Flow - Wong, Siew Fan (Curtin University, 2017)
The phenomena of emulsification process in the crude pipeline flow were investigated experimentally via Ultrasonic Velocity Profiler. The characterization study was conducted by analyzing the rheological behaviour and water-in-oil emulsions stability. The physics of the flow were examined by looking at the wall shear stress, Reynolds stress and turbulence intensity. The findings show Reynolds number, pipeline constriction ratio and water cuts result in the modified flow behaviour that has significant impact to the flow transport.